ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBASIS PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA MATERI ALAT-ALAT OPTIK - Mustika Zahfira Utami; Iwan Setiawan; Eko Risdianto; Elsa Viona (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2021)
The purpose of this study is to describe the analysis of the need for the development of digital comic learning media based on a contextual approach to increase learning motivation on optical instruments. This type of research is a research and development (R&D) research using the 3D research method (define, design, develop). In this study, the researcher limits it only to the define stage. The instrument used in this study was a questionnaire to analyze the needs of teachers and students of class XII MIPA and 6 physics teachers from SMA Negeri 2 Bengkulu City, SMA Negeri 4 Bengkulu City and SMA Negeri 9 Bengkulu CIty. Based on the results of the research conducted, it can be concluded that students need digital comic learning media based on a contextual approach to the material of optical instruments. This is based on the data obtained that 82.7% of students answered strongly agree and 83.3% of teachers answered that they agreed the need to develop digital comic learning media based on a contextual approach to increase learning motivation.